Análise da superfície de porcelanatos polidos por meio de microscopia de força atômica - Fernandes, Mérilin Cristina dos Santos (2010)
The porcelain stoneware tile is a ceramic product that has presented a great increase on production, since it had excellent technical properties and raised aesthetic performance. To improve its aesthetic characteristics, it is submitted to a polishing process that influences a lot of interested properties of the products, due mainly to changes observed on the superficial roughness. In this way, the roughness was investigated throughout the superficial polishing process of the glazed and unglazed (technical) porcelain stoneware tile and it was correlated with the gloss. For this, the Atomic Force Microscope (AFM) was used, being ideal to measure the roughness in nanometer scale and to visualize the nanotexture of many types of surface materials. The specular part of the gloss was measured through the equipment known as glossmeter. The results achieved shown that the technical porcelain stoneware tile in the first stage is more rough than the glazed. On the technical porcelain stoneware tile the roughness reduction was more accented between the grit 80 and 1000 stages, and the gloss was practically double between the first and the last (POLIDO) stages. The surface covering with the polymeric resin reduced significantly the product gloss, without it causes brusque alterations in superficial roughness. On the glazed porcelain stoneware tile the roughness reduction and the gloss increased occurred mainly between the grit 600 and 1800 stages. Between the grit 1800 and 8000 stages had not observed great changes on the roughness or gloss, showing that the polishing becomes unnecessary from the grit 1800. In general way, the gloss reduction occurred more visibly in stages of polishing with abrasives of larger grains, while the abrasives of smaller grains had given the final gloss, intervene poorly in roughness. The results interpretation had supplied subsidies to a better understanding and control of the process responsible for the final characteristics between the glazed and technical products, and the differences between these typologies.